2020
DOI: 10.9734/ejmp/2019/v30i430195
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Medicinal and Aromatic Plants Used in the Al-Hoceima Region (Northern Morocco)

Abstract: Objective: An ethnobotanical study of medicinal and aromatic plants was conducted in the region of Al-Hoceima (Morocco) to contribute to the knowledge of medicinal species used in traditional phytotherapy by the local population. Methodology: Using 100 questionnaire sheets, a series of ethnobotanical surveys were carried out in the field during April and May 2019 among ordinary users of the plants. The ethnobotanical survey was carried out using a probability (random) sampling method. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The present study shows that half of the pesticide plant species inventoried are grown in the farmers' fields or along the household fence, indicating that the inhabitants of Gitega were aware of the importance of these plants. These results are consistent with those in northern Morocco that most of the plants inventoried are grown in the fields (Brahim et al, 2020) in contrast to the study in Congo that showed that the most dominant pesticide plant species are found in the forest (Ipona et al, 2019)…”
Section: Habitat and Availability Of Pesticidal Plant Speciessupporting
confidence: 91%
“…The present study shows that half of the pesticide plant species inventoried are grown in the farmers' fields or along the household fence, indicating that the inhabitants of Gitega were aware of the importance of these plants. These results are consistent with those in northern Morocco that most of the plants inventoried are grown in the fields (Brahim et al, 2020) in contrast to the study in Congo that showed that the most dominant pesticide plant species are found in the forest (Ipona et al, 2019)…”
Section: Habitat and Availability Of Pesticidal Plant Speciessupporting
confidence: 91%
“…In the region of Al Hoceima, medicinal and aromatic plants hold profound and multifaceted importance, playing an essential role in the health and well-being of inhabitants as well as in preserving cultural tradition. These plants have been traditionally used by local populations to treat a diverse range of ailments, from minor afflictions to more serious illnesses [4]. The importance of aromatic plants in the Al Hoceima region also cannot be underestimated.…”
Section: Introductionmentioning
confidence: 99%